The Price of Capital, Factor Substitutability, and Corporate Profits - Philipp Hergovich; Monika Merz (Institute of Labor Economics (IZA), 2018)
The capital-to-labor ratio has steadily risen in the U.S. and elsewhere during the post-WWII period. Since the 1970s this rise has been accompanied by a rise in the level and variability of corporate profits whereas the labor share of income has declined. In this paper we ask whether these trends are related in that they can be explained by a common determinant such as the observed decline in the relative price of new capital goods, or the change in production technology towards in- creased factor substitutability. We use a dynamic stochastic equilibrium model of competitive search in the labor market augmented by a CES production function that allows firms to substitute between capital and labor at varying degrees. By assumption, firms can adjust capital more easily than labor. Profits arise from rents paid to quasi-fixed factors of production. We find that the declining relative price of capital and the increase in factor substitutability each causes the capital-to-labor ratio and the level and volatility of corporate profits to rise, but only increased factor substitutability generates the observed decrease in the labor share of income.
Keywords: E24; G32; J64; 330; factor substitutability; quasi-fixed production factor; competitive search; profits